Մի նշխար երաժիշտ-փիլիսոփա Ներսես վարդապետ Մոկացու երաժշտաբանաստեղծական ժառանգությունից - Մուշեղյան, Աստղիկ («Նաիրի» հրատ.)
Статья посвящена анализу одного из лучших образцов армянского средневекового песнетворчества – тагу (песнопению) “Радуется ныне гора Фавор”, исполняемому на праздник Преображения. Он появляется в рукописных источниках, начиная с XV века (самый ранний из известных нам – “Гандзаран”, 1476 г.) и является одним из наиболее популярных тагов. В некоторых рукописях его авторство приписывается архимандриту Нерсесу Мокаци (по прозвищу Матах), знаменитому церковному деятелю, поэту и музыканту, жившему в XV-XVI вв. This article is devoted to the analysis of one of the finest examples of Armenian medieval music – the tagh (canticle) Mount Tabor Rejoices Today («Այսօր ցնծայ լեառն Թաբօր»), performed at the Feast of the Transfiguration. The tagh appears in manuscripts from the 15th century onwards (the earliest known is Gandzaran, copied in 1476) and was one of the most popular taghs. In some manuscripts it is attributed to Archimandrite Nerses Mokatsi (nicknamed Matagh), a 15th-16th centuries prominent cleric, poet and musician.
Keywords: Արվեստ; Երգարվեստ